(3GdeNUUs - (3Ydj Hf ESeGYjd, GdeYQha H` GHf SjOg, CHh GdMSf,J (B458 (3g` s ((3eMeO Hf eMeO Hf CMeO GdhGSWi s)
(3ChdgG (B:s
(3heeG jchf GSekG ai HYV GdcdGe , hUaI ai HYVg (B: (3CaZi (B: (3bGd SjHhjg (B: (3gh ai GdCUd UaI LYdhg HefRdI TOjO s
(3BNQgG (B:s
(3hGdbOje HGdbjGS gh TF ReGfg ai GdeGVi CcHQ ef ReGf TF BNQ gh bGFe HGdbjGS gh TF ReGfg ai GdeGVi CcHQ ef ReGf TF BNQ gh bGFe HGdbjGS Edjg hGdbOje HMSH GdPGJ gh GdPi djS dg eHOC ced GdcJGH hGdMeO dhGgH GdYbd s
(3GdLRA (B16 (3cJH ai eQSjg ai Thb GdCfOdS haQZ efg Sfg (B599 (3hGdLRA (B17 (3cJHg GdhGSWi Sfg (B562s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B263 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B36s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B221 s
Keywords: (3GddZIs